Stronger than Steel : Spider silk DNA and the quest for better bulletproof vests, sutuers, and parachute rope - Heos, Bridget (Scientists in the field series, 2013)
"In The Spider Silk Scientists, readers enter Randy Lewis' lab where they come face to face with golden orb weaver spiders and genetically engineered goats, whose milk contains the proteins to spin spider silk--and to weave a nearly indestructible fiber. Learn how this amazing material might someday be used to repair or replace human ligaments and bones, improve body armor, strenghten parachute rope, and even tether an airplane to an aircraft carrier! Readers explore rapid advancements in the application of genetic medicine and their potential to save and improve lives while considering the crucial ethical concerns of genetic research. A timely addition to the acclaimed Scientists in the Field series. "--